Rocío Da Riva, Arqueólogos, etnólogos y espías. La misión de Leo Frobenius en Arabia y Eritrea (1914–1915). Barcelona, Bellaterra Arqueología, 2017. CLXXXIV + 184. ISBN 978– 84–7.290–830–7. €17.10 - Fernández Martínez, Víctor M. (2017)
Fil: Fernández Martínez, Víctor M. Universidad Complutense de Madrid; España